Fracture behavior of natural fiber reinforced biopolymer matrix composite - Yusof, Yusliza; Ahmad, Zuraida; Iis, Sopyan (Trans Tech Publications, Switzerland, 2008)
The attention in natural fiber reinforced biopolymer composite materials has been rapidly growing both in terms of industrial applications and basic research. This study was addressed to the investigation of the impact properties and fracture behaviour of biodegradable composites made from egg albumen reinforced by natural cotton fibres. The albumen-cotton composites have been fabricated by hands lay-up technique at varied volume fiber fraction from 2, 4, 6, 8, and 10 vol.% cotton. The specimens were cured at room temperature for a fixed time of 14 days to ensure the specimens are fully dried and harden, before being subjected to mechanical test. The cotton fibres have contributed in a significant improvement in fracture toughness of the composites. The obtained impact strength varied from 15.0 to 19.0 kJ/m2, and the fracture toughness varied from 0.7177 to 0.9453 J depending on vol.% cotton, with the optimum mechanical performance was obtained at 6 vol.% cotton. Morphological observation using SEM revealed that most of the fabricated specimens failed due to fiber breakage, pull out, and void growth.